Refleksi Arsitektur Vernakular Pada Bangunan Bantayo Pobo'ide Di Kabupaten Gorontalo - Eka, Rahmawati; Supu , Adam; Dwi Arini , Lutfiah (Program Studi Teknik Arsitektur, Fakultas Teknik, Universitas Ichsan Gorontalo, 2025)
The Bantayo Poboide traditional house is an important symbol of Gorontalo culture. In the social structure and traditional government of the Gorontalo people, this house is not only used as a residence or meeting hall, but also as a representation of noble values ​​that are inherited from generation to generation. The name Bantayo Poboide comes from two words in the Gorontalo language, namely